Cysts of the genus Protoperidinium species in sediments from coastal waters of Phu Yen, Khanh Hoa and Ninh Thuan provinces, South central Vietnam - Luom, Phan Tan; Lam, Nguyen Ngoc; Hai, Doan Nhu (Academia Journal of Biology, 2016)
Eight different types of cysts belonging to the genus Protoperidinium were recorded in sediments sampled at seven stations in the coastal waters of South Central Viet Nam. All types of cysts are firstly described and discussed in detail. Among them, Protoperidinium latissimum, P. conicum, P. cf. shanghaiense, and Protoperidinium sp.3 that have the saphopylic archeopyle type correspondent to 2a paraplate; P. parthenopes and Protoperidinium sp.2 (Islandinium brevispinosum) are characterized by a saphopylic archeopyle comprising three apical paraplates. Citation: Phan Tan Luom, Nguyen Ngoc Lam, Doan Nhu Hai, 2017. Cysts of the genus Protoperidinium species in sediments from coastal waters of Phu Yen, Khanh Hoa and Ninh Thuan provinces, south central Viet Nam. Tap chi Sinh hoc, 39(1): 32-39. DOI: 10.15625/0866-7160/v39n1.8403. *Corresponding author: luom.dt@gmail.com. Received 14 June 2016, accepted 20 March 2017